Developpements recents concernant l'elevage du betail trypanotolerant: Examen de l'etude FAO/CIPEA/PNUE sur le betail trypanotolerant - International Livestock Centre for Africa (International Livestock Centre for Africa, 1978)
Review of the progress made by FAO - ILCA - UNEP in studying trypanotolerant cattle in West and central Africa.